Correlation Analysis of Stress and Blood Pressure in Hypertensive Farm Laborers in the Mumbulsari Jember Health Center Working Area - Ida Srisurani Wiji Astuti; Fevi Meyta Kusumaning Rahenie; Yuli Hermansyah (Journal of Agromedicine and Medical Sciences, 2023)
Hypertension has a high prevalence of patients in the world, as well as in Mumbulsari Jember District. This is due to many risk factors for the incidence of hypertension and doesn’t cause significant symptoms. Psychological stress is one of the factors causing hypertension. Work, economic, and social problems are triggers for stress. This is experienced by farm laborers with complex problems that cause psychological stress conditions. The purpose of this study was to determine whether there is a correlation between stress and increased blood pressure in hypertensive farm laborers in the Mumbulsari Jember Health Center Working Area. This research is an analytic observational research with cross sectional study design. The sampling method was convenience sampling. The data used were primary data (Self Reporting Questionnaire 20 (SRQ-20)) and secondary data (medical records of patients in Puskesmas Mumbulsari Jember). The results of this study showed normal psychology, namely in 11 respondents (42.3%) experiencing stage 1 hypertension conditions and 15 respondents (57.7%) experiencing stage 2 hypertension. SRQ-20 results identified mental distress, namely 23 respondents (60.5%) experienced stage 1 hypertension and 15 respondents (39.5%) experienced stage 2 hypertension. The results of the analysis showed there was no significant correlation between stress and increased blood pressure in hypertensive farm laborers in the working area of the Mumbulsari Jember Health Center with a ρ-value of 0.151 (ρ>0.05). This study concluded that there is no correlation between stress and increased blood pressure in hypertensive farm laborers in the Mumbulsari Jember Health Center Working Area. Keywords: Hypertension, Stress, SRQ-20, Farm Laborer